Use, Practices and Attitudes of Sports Nutrition and Strength and Conditioning Practitioners towards Tart Cherry Supplementation - Vlad Sabou; Jimmy Wangdi; Mary F. O'Leary; Vincent G. Kelly; Joanna L. Bowtell (MDPI AG, 2020)
Tart cherry (TC) supplementation has been shown to accelerate post-exercise recovery, enhance endurance performance and improve sleep duration and quality. This study aimed to identify the use, practices and attitudes of sports nutrition and strength and conditioning practitioners towards tart cherry supplementation. Thirty-five practitioners anonymously completed an online survey investigating their use, practices and attitudes towards tart cherry supplements. Forty-six percent of the responders were currently recommending TC supplements, 11% had previously recommended TC supplements and 26% have not previously recommended TC supplements but were planning on doing so in the future. Of those recommending TC, 50% recommended or were planning on recommending TC supplements to enhance exercise recovery and 26% to improve sleep duration and quality. Acute supplementation and daily use during multi-day competition or demanding training blocks with a 2-3-day pre-load were the most reported supplementation recommendations (28% and 18%, respectively). Fifty-two percent of responders indicated uncertainty about the daily polyphenol dose to recommend as part of a TC supplementation protocol. Despite the high use and interest from sports nutrition and strength and conditioning practitioners in TC supplements, their practices did not align with the protocols found to be effective within the literature.